What is the derivative of (x^2)(sinx)(tanx) without using the chain rule?

2 Answers
Apr 13, 2015

You can manipulate your function remembering that:
tan(x)=sin(x)/cos(x)tan(x)=sin(x)cos(x)
and sin^2(x)=1-cos^2(x)sin2(x)=1cos2(x)
and get:
enter image source here
from this point onwards it is a piece of cake!!!
:-)

Apr 13, 2015

Use the product rule for three factors:

d/(dx)(fgh) = f'gh+fg'h+fgh'

For y = x^2sinxtanx, we get

y' = 2xsinxtanx + x^2 cosxtanx+x^2sinxsec^2x

We ca rewrite the middle term more simply, and we may choose to rewrite the third term:

y' = 2xsinxtanx + x^2 sinx+x^2tanxsecx.

d/(dx)(fgh) =f'[gh]+f d/(dx)[gh]

color(white)"sssssssss" =f'gh+f[g'h+gh']

color(white)"sssssssss" =f'gh+fg'h+fgh'.